The Dynamic Or Testicular Activity Of The Hard-Lipped Barb (Osteochilus Hasselti C.V.) Under Extended Photoperiod - A Wulandari; Soeminto Soeminto; Gratiana E Wijayanti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
Hormonal manipulation has been widely used in aquaculture to promote fish reproduction.  However some concern has been raised in accordance to it effect of human health as well as environmental issues.  Therefore alternative approaches in promoting fish reproduction need to be continuously studied.  Photoperiod manipulation offers a favorable alternative since it is one of the most crucial environmental cues necessary for fish reproduction.  An experimental study has been conducted to evaluate the effect of various photoperiods on testicular activities in the hard-lipped barb (Osteochilus hasselti C.V.).  Four groups of fish were reared under different photoperiod i.e. 14L:10D, 16L:8D, 18L:6D and the control group were reared under natural photoperiod for eight weeks period. Forth nightly three fish of each group were stripped to aspirate milt for measurement of milt volume and sperm concentration, they were decapitated for gonado-somatic index calculation and spermatogenic activities.  The results showed that the gonado somatic index (GSI) of the control group, 14L:10D and 18L:6D increased throughout the experimental period, meanwhile GSI of the fish reared under 16L:8D increased up to 4th week then decreased until the end of the study.  The fluctuation of the GSI values was followed by the fluctuation of milt volumes and sperm concentration.  This can be concluded that rising daily photoperiod up to 16 hours could improve reproduction in male hard-lipped barb.